Reducing Tobacco-Related Cancer Incidence and Mortality: Workshop Summary - Institute of Medicine (The National Academies Press, 2013)
Tobacco use is the leading cause of preventable death in United States, causing more than 440,000 deaths annually and resulting in $193 billion in health-related economic losses each year—$96 billion in direct medical costs and $97 billion in lost productivity. Since the first U.S. Surgeon General's report on smoking in 1964, more than 29 Surgeon General's reports, drawing on data from thousands of studies, have documented the overwhelming and conclusive biologic, epidemiologic, behavioral, and pharmacologic evidence that tobacco use is deadly. This evidence base links tobacco use to the development of multiple types of cancer and other life-threatening conditions, including cardiovascular and respiratory diseases. Smoking accounts for at least 30 percent of all cancer deaths, and 80 percent of lung cancer deaths. Despite the widespread agreement on the dangers of tobacco use and considerable success in reducing tobacco use prevalence from over 40 percent at the time of the 1964 Surgeon General's report to less than 20 percent today, recent progress in reducing tobacco use has slowed. An estimated 18.9 percent of U.S. adults smoke cigarettes, nearly one in four high school seniors smoke, and 13 percent of high school males use smokeless tobacco products. In recognition that progress in combating cancer will not be fully achieved without addressing the tobacco problem, the National Cancer Policy Forum of the Institute of Medicine (IOM) convened a public workshop, Reducing Tobacco-Related Cancer Incidence and Mortality, June 11-12, 2012 in Washington, DC. In opening remarks to the workshop participants, planning committee chair Roy Herbst, professor of medicine and of pharmacology and chief of medical oncology at Yale Cancer Center and Smilow Cancer Hospital, described the goals of the workshop, which were to examine the current obstacles to tobacco control and to discuss potential policy, outreach, and treatment strategies that could overcome these obstacles and reduce tobacco-related cancer incidence and mortality. Experts explored a number of topics, including: the changing demographics of tobacco users and the changing patterns of tobacco product use; the influence of tobacco use on cancer incidence and cancer treatment outcomes; tobacco dependence and cessation programs; federal and state level laws and regulations to curtail tobacco use; tobacco control education, messaging, and advocacy; financial and legal challenges to tobacco control efforts; and research and infrastructure needs to support tobacco control strategies, reduce tobacco related cancer incidence, and improve cancer patient outcomes. Reducing Tobacco-Related Cancer Incidence and Mortality summarizes the workshop.
Keywords: Health and Medicine

Assessing the Use of Agent-Based Models for Tobacco Regulation - Institute of Medicine (The National Academies Press, 2015)
Tobacco consumption continues to be the leading cause of preventable disease and death in the United States. The Food and Drug Administration (FDA) regulates the manufacture, distribution, and marketing of tobacco products - specifically cigarettes, cigarette tobacco, roll-your-own tobacco, and smokeless tobacco - to protect public health and reduce tobacco use in the United States. Given the strong social component inherent to tobacco use onset, cessation, and relapse, and given the heterogeneity of those social interactions, agent-based models have the potential to be an essential tool in assessing the effects of policies to control tobacco. Assessing the Use of Agent-Based Models for Tobacco Regulation describes the complex tobacco environment; discusses the usefulness of agent-based models to inform tobacco policy and regulation; presents an evaluation framework for policy-relevant agent-based models; examines the role and type of data needed to develop agent-based models for tobacco regulation; provides an assessment of the agent-based model developed for FDA; and offers strategies for using agent-based models to inform decision making in the future.
Keywords: Health and Medicine

Ending the Tobacco Problem: A Blueprint for the Nation - Institute of Medicine (The National Academies Press, 2007)
The nation has made tremendous progress in reducing tobacco use during the past 40 years. Despite extensive knowledge about successful interventions, however, approximately one-quarter of American adults still smoke. Tobacco-related illnesses and death place a huge burden on our society. Ending the Tobacco Problem generates a blueprint for the nation in the struggle to reduce tobacco use. The report reviews effective prevention and treatment interventions and considers a set of new tobacco control policies for adoption by federal and state governments. Carefully constructed with two distinct parts, the book first provides background information on the history and nature of tobacco use, developing the context for the policy blueprint proposed in the second half of the report. The report documents the extraordinary growth of tobacco use during the first half of the 20th century as well as its subsequent reversal in the mid-1960s (in the wake of findings from the Surgeon General). It also reviews the addictive properties of nicotine, delving into the factors that make it so difficult for people to quit and examines recent trends in tobacco use. In addition, an overview of the development of governmental and nongovernmental tobacco control efforts is provided. After reviewing the ethical grounding of tobacco control, the second half of the book sets forth to present a blueprint for ending the tobacco problem. The book offers broad-reaching recommendations targeting federal, state, local, nonprofit and for-profit entities. This book also identifies the benefits to society when fully implementing effective tobacco control interventions and policies.
Keywords: Health and Medicine

Scientific Standards for Studies on Modified Risk Tobacco Products - Institute of Medicine (The National Academies Press, 2012)
Smoking-related diseases kill more Americans than alcohol, illegal drugs, murder and suicide combined. The passage of the Family Smoking Prevention and Tobacco Control Act of 2009 gave the FDA authority to regulate "modified risk tobacco products" (MRTPs), tobacco products that are either designed or advertised to reduce harm or the risk of tobacco-related disease. MRTPs must submit to the FDA scientific evidence to demonstrate the product has the potential to reduce tobacco related harms as compared to conventional tobacco products. The IOM identifies minimum standards for scientific studies that an applicant would need to complete to obtain an order to market the product from the FDA.
Keywords: Health and Medicine

State Programs Can Reduce Tobacco Use - Institute of Medicine (The National Academies Press, 2000)
Keywords: Health and Medicine

Understanding the U.S. Illicit Tobacco Market: Characteristics, Policy Context, and Lessons from International Experiences - National Research Council (The National Academies Press, 2015)
Tobacco use has declined because of measures such as high taxes on tobacco products and bans on advertising, but worldwide there are still more than one billion people who regularly use tobacco, including many who purchase products illicitly. By contrast to many other commodities, taxes comprise a substantial portion of the retail price of cigarettes in the United States and most other nations. Large tax differentials between jurisdictions increase incentives for participation in existing illicit tobacco markets. In the United States, the illicit tobacco market consists mostly of bootlegging from low-tax states to high-tax states and is less affected by large-scale smuggling or illegal production as in other countries. In the future, nonprice regulation of cigarettes - such as product design, formulation, and packaging - could in principle, contribute to the development of new types of illicit tobacco markets. Understanding the U.S. Illicit Tobacco Market reviews the nature of illicit tobacco markets, evidence for policy effects, and variations among different countries with a focus on implications for the United States. This report estimates the portion of the total U.S. tobacco market represented by illicit sales has grown in recent years and is now between 8.5 percent and 21 percent. This represents between 1.24 to 2.91 billion packs of cigarettes annually and between $2.95 billion and $6.92 billion in lost gross state and local tax revenues. Understanding the U.S. Illicit Tobacco Market describes the complex system associated with illicit tobacco use by exploring some of the key features of that market - the cigarette supply chain, illicit procurement schemes, the major actors in the illicit trade, and the characteristics of users of illicit tobacco. This report draws on domestic and international experiences with the illicit tobacco trade to identify a range of possible policy and enforcement interventions by the U.S. federal government and/or states and localities.
Keywords: Behavioral and Social Sciences; Health and Medicine

Public Health Implications of Raising the Minimum Age of Legal Access to Tobacco Products - Institute of Medicine (The National Academies Press, 2015)
Tobacco use by adolescents and young adults poses serious concerns. Nearly all adults who have ever smoked daily first tried a cigarette before 26 years of age. Current cigarette use among adults is highest among persons aged 21 to 25 years. The parts of the brain most responsible for cognitive and psychosocial maturity continue to develop and change through young adulthood, and adolescent brains are uniquely vulnerable to the effects of nicotine. At the request of the U.S. Food and Drug Administration, Public Health Implications of Raising the Minimum Age of Legal Access to Tobacco Products considers the likely public health impact of raising the minimum age for purchasing tobacco products. The report reviews the existing literature on tobacco use patterns, developmental biology and psychology, health effects of tobacco use, and the current landscape regarding youth access laws, including minimum age laws and their enforcement. Based on this literature, the report makes conclusions about the likely effect of raising the minimum age to 19, 21, and 25 years on tobacco use initiation. The report also quantifies the accompanying public health outcomes based on findings from two tobacco use simulation models. According to the report, raising the minimum age of legal access to tobacco products, particularly to ages 21 and 25, will lead to substantial reductions in tobacco use, improve the health of Americans across the lifespan, and save lives. Public Health Implications of Raising the Minimum Age of Legal Access to Tobacco Products will be a valuable reference for federal policy makers and state and local health departments and legislators.
Keywords: Health and Medicine

Combating Tobacco Use in Military and Veteran Populations - Institute of Medicine (The National Academies Press, 2009)
The health and economic costs of tobacco use in military and veteran populations are high. In 2007, the Department of Veterans Affairs (VA) and the Department of Defense (DoD) requested that the Institute of Medicine (IOM) make recommendations on how to reduce tobacco initiation and encourage cessation in both military and veteran populations. In its 2009 report, Combating Tobacco in Military and Veteran Populations, the authoring committee concludes that to prevent tobacco initiation and encourage cessation, both DoD and VA should implement comprehensive tobacco-control programs.
Keywords: Health and Medicine

Clearing the Smoke: Assessing the Science Base for Tobacco Harm Reduction - Institute of Medicine (The National Academies Press, 2001)
Despite overwhelming evidence of tobacco's harmful effects and pressure from anti-smoking advocates, current surveys show that about one-quarter of all adults in the United States are smokers. This audience is the target for a wave of tobacco products and pharmaceuticals that claim to preserve tobacco pleasure while reducing its toxic effects. Clearing the Smoke addresses the problems in evaluating whether such products actually do reduce the health risks of tobacco use. Within the context of regulating such products, the committee explores key questions: Does the use of such products decrease exposure to harmful substances in tobacco? Is decreased exposure associated with decreased harm to health? Are there surrogate indicators of harm that could be measured quickly enough for regulation of these products? What are the public health implications? This book looks at the types of products that could reduce harm and reviews the available evidence for their impact on various forms of cancer and other major ailments. It also recommends approaches to governing these products and tracking their public health effects. With an attitude of healthy skepticism, Clearing the Smoke will be important to health policy makers, public health officials, medical practitioners, manufacturers and marketers of "reduced-harm" tobacco products, and anyone trying to sort through product claims.
Keywords: Health and Medicine

Public Health Consequences of E-Cigarettes - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Millions of Americans use e-cigarettes. Despite their popularity, little is known about their health effects. Some suggest that e-cigarettes likely confer lower risk compared to combustible tobacco cigarettes, because they do not expose users to toxicants produced through combustion. Proponents of e-cigarette use also tout the potential benefits of e-cigarettes as devices that could help combustible tobacco cigarette smokers to quit and thereby reduce tobacco-related health risks. Others are concerned about the exposure to potentially toxic substances contained in e-cigarette emissions, especially in individuals who have never used tobacco products such as youth and young adults. Given their relatively recent introduction, there has been little time for a scientific body of evidence to develop on the health effects of e-cigarettes. Public Health Consequences of E-Cigarettes reviews and critically assesses the state of the emerging evidence about e-cigarettes and health. This report makes recommendations for the improvement of this research and highlights gaps that are a priority for future research.
Keywords: Health and Medicine

Review of EPA's 2022 Draft Formaldehyde Assessment - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Formaldehyde is widely present in the environment and is one of the highest production chemicals by volume, used in manufactured goods including wood products, permanent press fabrics, and household products. It is also formed by combustion sources and is present in smoke from cigarettes and other tobacco products, and in emissions from gas stoves and open fireplaces. In carrying out its mission to protect human health, the U.S. Environmental Protection Agency (EPA) identifies and characterizes the health hazards of chemicals found in the environment through its Integrated Risk Information System (IRIS) Program, which has reviewed the human health hazards resulting from formaldehyde exposure in several assessments. This report is a continuation of guidance from the National Academies on draft IRIS assessments of formaldehyde and other aspects of the IRIS program. This report reviews the 2022 Draft Assessment with regard to its adequacy and transparency in evaluating the scientific literature, use of appropriate methods to synthesize the current state-of-the science, and presentations of conclusions that are supported by the scientific evidence. The report concludes that the 2022 Draft Assessment follows the advice of prior National Academies reports and that its findings on hazard and quantitative risk are supported by the evidence identified. However, revisions are needed to ensure that users can find and follow the methods used in each step of the assessment for each health outcome.
Keywords: Environment and Environmental Studies

Spread, Scale, and Sustainability in Population Health: Workshop Summary - Institute of Medicine (The National Academies Press, 2015)
Spread, Scale, and Sustainability in Population Health is the summary of a workshop convened by the Institute of Medicine's Roundtable on Population Health Improvement in December 2014 to discuss the spread, scale, and sustainability of practices, models, and interventions for improving health in a variety of inter-organizational and geographical contexts. This report explores how users measure whether their strategies of spread and scale have been effective and discusses how to increase the focus on spread and scale in population health.
Keywords: Health and Medicine

Fulfilling the Potential of Cancer Prevention and Early Detection: An American Cancer Society and Institute of Medicine Symposium - Institute of Medicine; National Research Council (The National Academies Press, 2004)
This report is the summary of a symposium presented by the American Cancer Society (ACS) and the Institute of Medicine (IOM) to further disseminate the conclusions and recommendations of Fulfilling the Potential of Cancer Prevention and Early Detection. This report discusses issues including better support for tobacco and obesity campaigns; coordination of programs; joint approaches with the food industry; the need for an explicit consensus national tobacco and obesity strategy; viewpoints of payers; changing Medicare's approach to prevention; private sector payment programs; improvements in applied research and dissemination of results; better science in programs; problems in modifying medical practice; and conflict between individual choice and policy options.
Keywords: Health and Medicine

Clearing the Air: Asthma and Indoor Air Exposures - Institute of Medicine (The National Academies Press, 2000)
Since about 1980, asthma prevalence and asthma-related hospitalizations and deaths have increased substantially, especially among children. Of particular concern is the high mortality rate among African Americans with asthma. Recent studies have suggested that indoor exposures—to dust mites, cockroaches, mold, pet dander, tobacco smoke, and other biological and chemical pollutants—may influence the disease course of asthma. To ensure an appropriate response, public health and education officials have sought a science-based assessment of asthma and its relationship to indoor air exposures. Clearing the Air meets this need. This book examines how indoor pollutants contribute to asthma—its causation, prevalence, triggering, and severity. The committee discusses asthma among the general population and in sensitive subpopulations including children, low-income individuals, and urban residents. Based on the most current findings, the book also evaluates the scientific basis for mitigating the effects of indoor air pollutants implicated in asthma. The committee identifies priorities for public health policy, public education outreach, preventive intervention, and further research.
Keywords: Environment and Environmental Studies; Health and Medicine

How Far Have We Come in Reducing Health Disparities?: Progress Since 2000: Workshop Summary - Institute of Medicine (The National Academies Press, 2012)
At the turn of the 21st century, several important reports and events designed to raise awareness of health disparities and to describe initial efforts to reduce health disparities took place. The Surgeon General's office released several reports that showed dramatic disparities in tobacco use and access to mental health services by race and ethnicity. The first real legislation focused on reducing health disparities was signed into law, creating the National Center for Minority Health and Health Disparities within the NIH. In 2001, the IOM released its landmark report, Crossing the Quality Chasm: A New Health System for the 21st Century, highlighting the importance of a focus on health care quality rather than a focus on only access and cost issues. Building upon these reports and events, the IOM held a workshop on April 8, 2010, that discussed progress to address health disparities and focused on the success of various federal initiatives to reduce health disparities. How Far Have We Come in Reducing Health Disparities? summarizes the workshop and explains the progress in the field since 2000.
Keywords: Health and Medicine

Review of the Formaldehyde Assessment in the National Toxicology Program 12th Report on Carcinogens - National Research Council (The National Academies Press, 2014)
Many people in the United States are exposed to formaldehyde. Exposure can occur from environmental sources (for example, combustion processes, building materials, and tobacco smoke) or in occupational settings (for example, the furniture, textile, and construction industries). Formaldehyde exposure also has endogenous sources—it is produced intracellularly as a component of the one carbon pool intermediary metabolism pathway. Scientists have studied formaldehyde for decades to determine whether exogenous formaldehyde exposure may be associated with cancer in humans. In 1981, The National Toxicology Program (NTP) first listed formaldehyde in the 2nd Report on Carcinogens as "reasonably anticipated to be a human carcinogen". In 2011, NTP upgraded the listing of formaldehyde to "known to be a human carcinogen". Following the new listing, Congress directed the Department of Health and Human Services to arrange for the National Academy of Sciences to independently review formaldehyde's substance profile and listing. This report presents the findings and conclusions of the committee formed in response to the congressional request. Review of the Formaldehyde Assessment in the National Toxicology Program 12th Report on Carcinogens concurs with NTP that there is sufficient evidence in studies that had adequate characterization of relevant exposure metrics to enable a strong conclusion about the association between formaldehyde exposure and cancer in humans. Additionally, the authoring committee independently reviewed the scientific evidence from studies in humans, experimental animals, and other studies relevant to the mechanisms of carcinogenesis and made level-of-evidence conclusions. This report finds clear and convincing epidemiologic evidence of an association between formaldehyde exposure and nasopharyngeal and sinonasal cancers in humans.
Keywords: Environment and Environmental Studies

Legal Strategies in Childhood Obesity Prevention: Workshop Summary - Institute of Medicine (The National Academies Press, 2011)
Since 1980, childhood obesity rates have more than tripled in the United States. Recent data show that almost one-third of children over 2 years of age are already overweight or obese. While the prevalence of childhood obesity appears to have plateaued in recent years, the magnitude of the problem remains unsustainably high and represents an enormous public health concern. All options for addressing the childhood obesity epidemic must therefore be explored. In the United States, legal approaches have successfully reduced other threats to public health, such as the lack of passive restraints in automobiles and the use of tobacco. The question then arises of whether laws, regulations, and litigation can likewise be used to change practices and policies that contribute to obesity. On October 21, 2010, the Institute of Medicine (IOM) held a workshop to bring together stakeholders to discuss the current and future legal strategies aimed at combating childhood obesity. Legal Strategies in Childhood Obesity Prevention summarizes the proceedings of that workshop. The report examines the challenges involved in implementing public health initiatives by using legal strategies to elicit change. It also discusses circumstances in which legal strategies are needed and effective. This workshop was created only to explore the boundaries of potential legal approaches to address childhood obesity, and therefore, does not contain recommendations for the use of such approaches.
Keywords: Food and Nutrition; Health and Medicine

The Health Effects of Cannabis and Cannabinoids: The Current State of Evidence and Recommendations for Research - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
Significant changes have taken place in the policy landscape surrounding cannabis legalization, production, and use. During the past 20 years, 25 states and the District of Columbia have legalized cannabis and/or cannabidiol (a component of cannabis) for medical conditions or retail sales at the state level and 4 states have legalized both the medical and recreational use of cannabis. These landmark changes in policy have impacted cannabis use patterns and perceived levels of risk. However, despite this changing landscape, evidence regarding the short- and long-term health effects of cannabis use remains elusive. While a myriad of studies have examined cannabis use in all its various forms, often these research conclusions are not appropriately synthesized, translated for, or communicated to policy makers, health care providers, state health officials, or other stakeholders who have been charged with influencing and enacting policies, procedures, and laws related to cannabis use. Unlike other controlled substances such as alcohol or tobacco, no accepted standards for safe use or appropriate dose are available to help guide individuals as they make choices regarding the issues of if, when, where, and how to use cannabis safely and, in regard to therapeutic uses, effectively. Shifting public sentiment, conflicting and impeded scientific research, and legislative battles have fueled the debate about what, if any, harms or benefits can be attributed to the use of cannabis or its derivatives, and this lack of aggregated knowledge has broad public health implications. The Health Effects of Cannabis and Cannabinoids provides a comprehensive review of scientific evidence related to the health effects and potential therapeutic benefits of cannabis. This report provides a research agenda—outlining gaps in current knowledge and opportunities for providing additional insight into these issues—that summarizes and prioritizes pressing research needs.
Keywords: Health and Medicine

Vital Directions for Health & Health Care: An Initiative of the National Academy of Medicine - National Academy of Medicine (The National Academies Press, 2017)
What can be more vital to each of us than our health? Yet, despite unprecedented health care spending, the U.S. health system is substantially underperforming, especially with respect to what should be possible, given current knowledge. Although the United States is currently devoting 18% of its Gross Domestic Product to delivering medical care—more than $3 trillion annually and nearly double the expenditure of other advanced industrialized countries—the U.S. health system ranked only 37 in performance in a World Health Organization assessment of member nations. In Vital Directions for Health & Health Care: An Initiative of the National Academy of Medicine, the National Academy of Medicine (NAM), which has long stood as the nation’s most trusted independent source of guidance in health, health care, and biomedical science, has marshaled the wisdom of more than 150 of the nation’s best researchers and health policy experts to assess opportunities for substantially improving the health and well-being of Americans, the quality of care delivered, and the contributions of science and technology. This publication identifies practical and affordable steps that can and must be taken across eight action and infrastructure priorities, ranging from paying for value and connecting care, to measuring what matters most and accelerating the capture of real-world evidence. Without obscuring the difficulty of the changes needed, in Vital Directions, the NAM offers an important blueprint and resource for health, policy, and leaders at all levels to achieve much better health outcomes at much lower cost.
Keywords: Health and Medicine